Punctuation: from teaching to assessment - Santos, Ana Lúcia (2019)
This paper explores the relevancy of punctuation as a key element establishing a connection between grammar and writing instruction. It explores common conceptions of punctuation, which connect the use of the comma to prosody, contrasting it with present rules for Portuguese, which assume a syntactic definition of the contexts in which a comma should be used or must be avoided. The paper shows that teachers working with different grades show distinct awareness levels of the relevance of syntax in the field of punctuation. In general, low awareness concerning this association results in a holistic view of punctuation instruction. We explore to what extent the national curriculum and national exams reflect this holistic view. The text ends with a positive note, summarizing recent advances in national exams, which will certainly impact on teaching practices.